Extreme points of the unit ball of an operator space - Kaneda, M. (Nazarbayev University, 2013)
Answering Pedersen’s question, I characterized extreme points of the unit ball of an operator space introducing the new notion “quasi-identity”. An application of extreme points is also given in
Keywords: first research week; operator spaces; extreme points